Peningkatan Kemandirian dan Kesejahteraan Penghuni Rumah Kasih Harmoni Paya Jaras Melalui Program Pengabdian Masyarakat Internasional - Saleh, M; Rasyidin, M; Wahyuni, Sri; Saputra, Al Mahfud; Nurhayati; Rizal, Muhammad (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The Community Service Program, titled "International Visit and Community Service at Rumah Kasih Harmoni Paya Jaras," aims to enhance the welfare of the residents at Rumah Kasih Harmoni, an orphanage located in Sungai Buloh, Selangor, Malaysia. The program was initiated in response to the financial challenges faced by Rumah Kasih Harmoni in fulfilling the basic needs of its residents. The objectives are to improve the funding sources for Rumah Kasih Harmoni, provide training and skill development for the residents, expand their knowledge and awareness, and foster a sustainable partnership between the proposing team and Rumah Kasih Harmoni. The methods employed include direct visits and interactions, educational and interactive activities, artistic and creative endeavors, physical and sports activities, along with social and cultural events. Active participation from the residents is encouraged throughout the program. The results include an increase in funding, enhanced skills and independence among the residents, improved knowledge and awareness, and the establishment of a robust, long-term collaboration between the proposing team and Rumah Kasih Harmoni.